Top lesson from COVID for solar geoengineering: Anticipatory research is needed - Jinnah, Sikina; Long, Jane C. S. (Frontiers in Climate, 2022)
This perspective article argues that anticipatory research into possible “emergency” response measures such as solar geoengineering will increase knowledge, and thus confidence, in any future decisions to either deploy or reject these technologies. Similarities between COVID and climate can reveal some perspective on the benefits of anticipatory vaccine research for anticipatory for solar geoengineering research. Although we deeply hope governments will aggressively reduce emissions and scale up adaptation efforts in time to avoid the worst climate impacts, we argue that the benefits of anticipatory solar geoengineer research currently outweigh the risks of not moving research forward.